Mapping Traditional Games as Ethnopedagogical Resources for Cultural Sustainability in Southeast Sulawesi, Indonesia - Tri Indah Rusli; Yuliyanah Sain; Rohmiati Rohmiati; Noor Azlan Ahmad Zanzali (Universitas Muhammadiyah Mataram, 2026)
Traditional games represent an important repository of local wisdom and serve as ethnopedagogical resources that transmit cultural values, social norms, and indigenous knowledge across generations. Their decline therefore poses a serious threat not only to cultural continuity but also to culturally grounded learning practices. In Southeast Sulawesi (Bumi Anoa), Indonesia, the increasing dominance of digital play has significantly reduced children’s engagement with traditional games, weakening ethnopedagogical transmission. This study addresses this gap by examining: (1) The distribution and currenct status of traditional games in South east Sulawesi, (2) Their embedded ethnopedagogical values and (3) their continuity in children’s practices. Employing a qualitative multiple-site case study design, data were collected across 17 regencies and cities through field observation, semi-structured interviews with 20 cultural practitioners and community members, educator, researcher and document analysis. The data were analyzed thematically to reveal cultural meanings, pedagogical values, and transmission patterns embedded in the games. The results show that 38 traditional games were identified across 17 regencies and cities in Southeast Sulawesi, with approximately 90% no longer actively played by children, indicating a significant disruption in ethnopedagogical transmission. While many games share structural similarities with traditional games from other regions, linguistic variations reflect strong localized cultural identities. Only about 10% of the games persist, primarily through adult-led cultural performances or competitions, and institutional documentation remains fragmented and limited. This study contributes a comprehensive regional mapping that bridges cultural documentation and integration of Traditional games into culturally responsive learning to sustain local wisdom in digitalized context.